PROTEASE ACTIVITY OF THERMOPHILIC BACTERIA FROM LEJJA HOT SPRINGS IN SOPPENG SOUTH SULAWESI - Hafsan, Hafsan; Ramadani, Kurnia; Abbas, Abbas (Universitas Pendidikan Ganesha, 2021)
This research aimed to observe quantitatively the effect of temperature and pH on protease activities from thermophilic bacteria collected from Lejja—Hot springs. Spectrophotometry on the casein substrate was used to test the proteolytic activity of the crude protease. Mixtures of enzyme and casein were incubated at various temperatures and pH for 20 minutes. The absorbance of tyrosine from protein hydrolysis was determined by spectrophotometry on λ 280 nm. Temperature and pH impacted on protease activity were determined at temperature (60; 65; 70; 75; 80; 85 and 90oC) and pH (6.0; 6.5; 7.0; 7.5; 8, 0; 8,5 and 9,0). Results showed that treatment of temperature variations and pH had a significant effect on protease activity. Crude extract of Bacillus licheniformis protease showed that the highest activity at 80oC and pH 7.5 was 0.1303 unit/ml/minute. Bacillus stearoformis showed the highest enzymatic activity of the protease at 85oC, and pH 7.5 was 0.1226 Unit/ ml/minute. In comparison, Bacillus coagulans reached optimum activity at 75oC, and pH 7.5 was 0.2052 Unit/ml/minute. Isolates of Bacillus licheniformis, B. coagulans and B. stearoformis are bacteria that produce thermostable protease enzymes that can be developed as a source of genes and as a producer of the enzyme itself.